Quantitative Approximation Properties for Iterates of Moment Operator - Bardaro, Carlo; Faina, Loris; Mantellini, Ilaria (Mathematical Modelling and Analysis, 2015)
Here we state a quantitative approximation theorem by means of nets of certain modified Hadamard integrals, using iterates of moment type operators, for functions f defined over the positive real semi-axis ]0, +∞[, having Mellin derivatives. The main tool is a suitable K-functional which is compatible with the structure of the multiplicative group ]0, +∞[. Some numerical examples and graphical representations are illustrated.